Assessment of Young Dong tributary and Imgok Creek impacted by Young Dong coal mine, South Korea - Lee, B.T.; Ranville, J.F.; Wildeman, T.R.; Jang, M.; Shim, Y.S.; Ji, W.H.; Park, H.S.; Lee, H.J. (2012)
An initial reclamation of the Young Dong coal mine site, located in northeastern South Korea, was completed in 1995. Despite the filling of the adit with limestone, acid rock drainage (ARD) enters Young Dong tributary and is then discharged to Imgok Creek. This ARD carries an average of 500 mg CaCO 3/l of mineral acidity, primarily as Fe(II) and Al. Before spring runoff, the flow of Imgok Creek is 3.3-4 times greater than that of the tributary and has an alkalinity of 100 mg CaCO 3/l, which is sufficient to eliminate the mineral acidity and raise the pH to about 6.5. From April through September 2008, there were at least two periods of high surface flow that affects the flow of ARD from the adit. Flow of ARD reaches 2.8 m 3/min during spring runoff. This raised the concentrations of Fe and Al in the confluence with Imgok Creek. However, by 2 km downstream the pH of the Imgok Creek is 6.5 and only dissolved Fe is above the Korean drinking water criteria (0.30 mg/l). This suggests only a minor impact of Young Dong Creek water on Imgok Creek. Acid digestion of the sediments in Imgok Creek and Young Dong Tributary reveals considerable abundances of heavy metals, which could have a long-term impact on water quality. However, several water-based leaching tests, which better simulate the bioavailable metals pool, released only Al, Fe, Mn, and Zn at concentrations exceeding the criteria for drinking water or aquatic life. Â© 2011 Springer Science+Business Media B.V.